Kidney Biopsy Adequacy: A Metric-based Study. (January 2019) - Ferrer, German; Andeen, Nicole K.; Lockridge, Joseph; Norman, Douglas; Foster, Bryan R.; Houghton, Donald C.; Troxell, Megan L.
Abstract : There are differences in renal biopsy yield related to on-site evaluation, tissue division, and operator, among others. To understand these variations, we collected adequacy-associated data (%cortex, glomeruli, arteries, length) from consecutive native and allograft kidney biopsies over a 22-month period. In total, 1332 biopsies (native: 873, allograft: 459) were included, 617 obtained by nephrologists, 663 by radiologists, and 559 with access to on-site division. Proceduralists with access to on-site evaluation had significantly lower inadequacy rates and better division of tissue for light microscopy (LM), immunofluorescence, and electron microscopy than those without access to on-site evaluation. Radiologists in our region were significantly less likely to have access to on-site evaluation than nephrologists. On multivariate analysis for native kidney biopsies, the effect of having a radiologist perform the biopsy and having access to on-site division were both significant predictors of obtaining greater calculated amount of cortex for LM. Despite the trend for radiologists to obtain more tissue in general, biopsies from nephrologists contained a greater percentage of cortex and were more likely to be considered adequate for LM (native kidney inadequacy rate for LM: 1.11% vs. 5.41%, P =0.0086). Biopsies in which inadequate or marginal cortical tissue was submitted for LM had only minor decreases in the amount of cortex submitted for immunofluorescence and electron microscopy, revealing an opportunity for improved specimen triaging when limited tissue is obtained. In conclusion, both on-site evaluation/division and proceduralist significantly affect quantitative kidney biopsy metrics, which in turn affects the pathologist's ability to render an accurate diagnosis with appropriate prognostic information for the patient and treating nephrologist.